2014
DOI: 10.1007/978-3-319-02681-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Quality of Experience

Abstract: International audienceIn this chapter different factors that may influence Quality of Experience (QoE) in the context of media consumption, networked services, and other electronic communication services and applications, are discussed. QoE can be subject to a range of complex and strongly interrelated factors, falling into three categories: human, system and context influence factors (IFs). With respect to Human IFs, we discuss variant and stable factors that may potentially bear an influence on QoE, either f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 57 publications
1
132
0
5
Order By: Relevance
“…For instance, Reiter et al [21]have shown that age, sex and socio-economic status are all factors influencing QoE, while Kara et al [22] claim that economic context such as the brand perception of viewing device (in their case a smartphone) and the price, if any, paid to view the content were significant factors. However, such factors are also difficult to manage and correlate in a unified model for efficient, real-time systems.…”
Section: ) Subjective Qoe Assessment and Modelsmentioning
confidence: 99%
“…For instance, Reiter et al [21]have shown that age, sex and socio-economic status are all factors influencing QoE, while Kara et al [22] claim that economic context such as the brand perception of viewing device (in their case a smartphone) and the price, if any, paid to view the content were significant factors. However, such factors are also difficult to manage and correlate in a unified model for efficient, real-time systems.…”
Section: ) Subjective Qoe Assessment and Modelsmentioning
confidence: 99%
“…Futhermore, network-centric monitoring does not consider the multi-dimensional aspects of QoE. Beyond the network attributes, these aspects include the application, the system, the context and the user behavior itself [36]. This consideration is particularly highlighted in [39], where QoE is represented as a multi-layered vector.…”
Section: Qos/qoe Monitoring Systemsmentioning
confidence: 99%
“…Those probes will then be monitored centrally. Such an approach may have benefits in terms of end-to-end QoE delivery because it provides ISPs with information related to context-, system-and user-influencing factors (including the geographical location) [36], which relates to the principles of context-aware QoE monitoring. Centralized monitoring systems can utilize cloud technologies to reduce network-wide equipment costs and resolve programmability and flexibility issues.…”
Section: Cloud Processing -Issues Of Scalability and Securitymentioning
confidence: 99%
“…[10], [11]). Three key factors have been shown to influence these dependent variables, namely: human factors, the characteristics of the individual; system factors, the characteristics of the media, device and network used; and contextual factors, additional characteristics such as time, task, and local conditions [12].…”
Section: Related Workmentioning
confidence: 99%